Class attendance and university performance - Anna-Lena Hoffmann; Katharina Lerche (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2016)
Using survey data collected at Göttingen University, Germany, this paper evaluates the effect of attending the lecture and/or tutorial on the grade achieved in two basic courses in business administration and economics. The analysis shows that going to class has no significant impact on student performance in most specifications. Although the identification of a causal effect may not be possible with the data at hand, the results suggest that, in the given framework, attending class and studying on ones own may be substitutes.
Keywords: A22; H00; I21; 330; class attendance; economic education; tertiary education; university performance